2018
DOI: 10.1155/2018/1843142
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Ginseng Clinical Trials Registered in the WHO International Clinical Trials Registry Platform

Abstract: Although ginseng has long been broadly used in clinical settings around the world, few clinical trials on ginseng have been conducted. The objective of this study was to provide a comprehensive evaluation of the characteristics of ginseng clinical trials registered in the WHO International Clinical Trials Registry Platform (ICTRP) as of December 2017 regarding their frequency, design, type of ginseng, dosage, duration, condition, funding sources, and publication status. A total of 134 ginseng clinical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
14
0
3
Order By: Relevance
“…Ginseng has attracted the public attention in modern society due to its health benefits and commercial value. It has the effect to strengthen energy, enhance intelligence and body function, and promote longevity (He et al, ; Wu et al, ). The quality of ginseng is usually influenced by many conditions, such as age, cultivars, climate, medicinal parts, etc .…”
Section: Ms‐based Metabolomics Analysis In Herbal Bioactive Ingredientsmentioning
confidence: 99%
“…Ginseng has attracted the public attention in modern society due to its health benefits and commercial value. It has the effect to strengthen energy, enhance intelligence and body function, and promote longevity (He et al, ; Wu et al, ). The quality of ginseng is usually influenced by many conditions, such as age, cultivars, climate, medicinal parts, etc .…”
Section: Ms‐based Metabolomics Analysis In Herbal Bioactive Ingredientsmentioning
confidence: 99%
“…A number of modern drugs originate from traditional medications [ 16 ]. Ginseng has been used in clinical settings all over the world [ 17 ] and may provide the basis for the development of novel therapeutic agents. The objective of this article is to review the state of ginseng research and to evaluate the use of its bioactive compounds as therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, potential pharmacological interference with conventional drugs may be common and remains poorly investigated. For instance, high quality evidence about the clinical efficacy of Pannax ginseng, Lycium barbarum and Cinnamon, the three most extensively exported Chinese herbs, is practically non-existent [89][90][91]. Moreover, a comprehensive report of Cochrane reviews on Chinese herbal medicines (CHM) suggested that only 16% of all included primary studies use adequate sequence generation.…”
Section: Tcm Therapeutics-forgotten Treasure or Pandora's Box?mentioning
confidence: 99%